Sciences and Arts: commonalities and differences in CLIL - Carreras-Pérez-Aradros, Roberto (My University, 2022)
The differences between Arts and Sciences subjects exist not only in the content taught, but also in the methodologies followed by the teachers. These methodologies imply the use of specific resources, materials and even assessment methods whose goals and intentions to achieve the educational objectives are different. There is a vast literature devoted to the analysis and research in new methods to improve the acquisition of knowledge and skills in Sciences or Social Studies. Little by little the implementation of those new methods allows the development of the teaching practice of educators. In the recent years, Content and Language Integrated Learning (CLIL) programmes have appeared as a new approach to the learning of languages in the context of content subjects. The innovations and new methodologies of this approach have been revisited and improved through rigorous, sustainable and transparent theoretical studies in order to explore practical applications to different subjects, depending on the interest of the authors. However, the gap between Sciences and Arts still exists. The main objective of the present research is the observation and analysis of the teaching practice of teachers of different subjects in a CLIL programme in order to compare whether there are significant differences between specific aspects of those subjects. The aspects observed will be the teacher’s discourse, materials and resources, and assessment methods. The methodology followed to collect all data is based on the use of surveys and direct observation checklists, all of them with a rating scale to help the participants fill in the questionnaires. Despite the sample size, the results obtained highlighted the existing differences between Arts and Sciences in some of the items observed. However, those differences were not directly related to the CLIL methodologies but to the subjects themselves, as they need specific teaching practices to achieve the educational objectives proposed in each subject.
Keywords: CLIL; assessment methods; teacher’s discourse; materials; resources; Máster Universitario en Educación Bilingüe